2015
DOI: 10.1093/icvts/ivv344
|View full text |Cite
|
Sign up to set email alerts
|

The impact of angiotensin II type 1 receptor antibodies on post-heart transplantation outcome in Heart Mate II bridged recipients

Abstract: Our data showed no difference in the overall post-heart transplant survival and freedom from acute cellular and antibody-mediated rejection between anti-AT1R-negative and anti-AT1R-positive recipients. Further research is needed to assess the role of anti-AT1R antibodies in the risk stratification of LVAD-bridged recipients on the post-heart transplantation outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…A recent study found that VAD implantation was not associated with sensitization to MICA [2]. On the other hand, patients bridged with LVAD appeared to have higher titers of anti-AT1R antibodies compared to unsupported patients [18] although this increase did not portend reduced graft survival. In the present study, VAD was associated with poorer outcomes (Table S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that VAD implantation was not associated with sensitization to MICA [2]. On the other hand, patients bridged with LVAD appeared to have higher titers of anti-AT1R antibodies compared to unsupported patients [18] although this increase did not portend reduced graft survival. In the present study, VAD was associated with poorer outcomes (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the view of a broad B cell activation rather than stimulation through exposure to distinctive antigens. We propose that the humoral response induced by VAD support is a consequence of a systemic immune activation that leads to the generation of anti-HLA and non-HLA IgG including IgG Nabs along with anti-AT1R [18], - albumin [29], -phospholipids [30] and clinically irrelevant antibodies binding to HLA-coated beads [31]. In addition, the biomaterials used in the implanted devices are known to activate endothelial, coagulation and fibrinolytic pathways [32] and could plausibly contribute to sensitization in such a non-antigen specific manner [33].…”
Section: Discussionmentioning
confidence: 99%
“…Non‐HLA antibodies such as antibodies against AT1R, vimentin, myosin, and other endothelial cell (EC) antigens are prevalent among ventricular assist device (VAD) patients . Anti‐AT1R antibodies are known to initiate coagulation and inflammatory responses independent of the complement cascade .…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐AT1R antibodies are known to initiate coagulation and inflammatory responses independent of the complement cascade . There are conflicting reports about whether anti‐AT1R and EC antibodies play a role in cardiac allograft survival …”
Section: Introductionmentioning
confidence: 99%
“…Over 60% of heart transplant candidates who were AT1R negative prior to LVAD implantation developed de novo AT1R antibodies after the procedure independent of blood product usage 57 . Development of AT1R antibodies post-LVAD did not impact incidence of rejection or transplant survival.…”
Section: Introductionmentioning
confidence: 99%